[beta]-Glucan Synthesis in the Cotton Fiber (I. Identification of [beta]-1,4- and [beta]-1,3-Glucans Synthesized in Vitro). - Okuda, K. (1993)
In vitro [beta]-glucan products were synthesized by digitonin-solubilized enzyme preparations from plasma membrane-enriched fractions of cotton (Gossypium hirsutum) fiber cells. The reaction mixture favoring [beta]-1,4-glucan synthesis included the following effectors: Mg2+, Ca2+, cellobiose, cyclic-3[prime]:5[prime]-GMP, and digitonin. The ethanol insoluble fraction from this reaction contained [beta]-1,4-glucan and [beta]-1,3-glucan in an approximate ratio of 25:69. Approximately 16% of the [beta]-1,4-glucan was resistant to the acetic/nitric acid reagent. The x-ray diffraction pattern of the treated product favoring [beta]-1,4-glucan synthesis strongly resembled that of cellulose II. On the basis of methylation analysis, the acetic/nitric acid reagent-insoluble glucan product was found to be exclusively [beta]-1,4-linked. Enzymic hydrolysis confirmed that the product was hydrolyzed only by cellobiohydrolase I. Autoradiography proved that the product was synthesized in vitro. The degree of polymerization (DP) of the in vitro product was estimated by nitration and size exclusion chromatography; there were two average DPs of 59 (70%) and 396 (30%) for the [beta]-1,3-glucanase-treated sample, and an average DP of 141 for the acetic/nitric acid reagent-insoluble product. On the basis of product analysis, the positive identification of in vitro-synthesized cellulose was established.